To solve the quadratic equation \(-x^2 + x = -10\), we can first rearrange it into standard form:
\[ -x^2 + x + 10 = 0 \]
Multiplying the entire equation by -1 gives us:
\[ x^2 - x - 10 = 0 \]
Now we can use the quadratic formula to find the solutions. The quadratic formula is given by:
\[ x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \]
In our equation \(x^2 - x - 10 = 0\), the coefficients are:
- \(a = 1\)
- \(b = -1\)
- \(c = -10\)
Now we substitute these values into the quadratic formula:
-
Calculate the discriminant (\(b^2 - 4ac\)): \[ (-1)^2 - 4(1)(-10) = 1 + 40 = 41 \]
-
Calculate the two possible solutions using the quadratic formula: \[ x = \frac{-(-1) \pm \sqrt{41}}{2(1)} = \frac{1 \pm \sqrt{41}}{2} \]
Now we compute the two values:
\[ x = \frac{1 + \sqrt{41}}{2} \quad \text{and} \quad x = \frac{1 - \sqrt{41}}{2} \]
Calculating these values, we first find \(\sqrt{41} \approx 6.4\):
-
For \(x = \frac{1 + \sqrt{41}}{2}\): \[ x \approx \frac{1 + 6.4}{2} \approx \frac{7.4}{2} \approx 3.7 \]
-
For \(x = \frac{1 - \sqrt{41}}{2}\): \[ x \approx \frac{1 - 6.4}{2} \approx \frac{-5.4}{2} \approx -2.7 \]
Since the solutions to the quadratic equation are approximately \(x \approx 3.7\) and \(x \approx -2.7\), the only positive solution that matches the options provided is:
\[ \boxed{3.7} \]